PROGRAM BERSIH LINGKUNGAN DAN PENANAMAN TANAMAN TOGA DALAM MENINGKATKAN PELESTARIAN LINGKUNGAN DAN KESEHATAN MASYARAKAT - Arif Rachman Putra; Muhammad Jazuli; Didit Darmawan; Rahayu Mardikaningsih; Mila Hariani (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Environmental problems such as weed overgrowth and trash accumulation are still commonly found in public areas, particularly along the road connecting Tanggulangin and Jabon Districts. These conditions reduce environmental cleanliness and aesthetics and may negatively affect public health. This community service activity aimed to improve environmental preservation and support community health through an environmental clean-up program integrated with the planting of family medicinal plants (TOGA). The activity applied the Asset-Based Community Development (ABCD) approach, emphasizing local asset utilization and active community participation. The implementation stages included field observation, community coordination, environmental clean-up activities, and the planting of medicinal plants such as ginger, turmeric, galangal, and lemongrass on vacant land along the roadside. The results showed improvements in environmental cleanliness, orderliness, and aesthetics, along with increased public awareness and participation in maintaining environmental sustainability and supporting long-term community health.